Proposed key performance indicators in managing higher education: Case study in Indonesian higher education - Azis, Anton Mulyono; Wibisono, Dermawan (2010)
This paper propose key performance indicators in managing Indonesian higher education. This research is conducted to help Indonesian higher educations in increasing their competitiveness whereas to some extent Indonesian higher education tends to implement International Standard Organization (ISO) at the ceremonial level not to increase their performance. The paper provides a brief review of the current performance management systems framework in Indonesian higher education institution. The research is conducted by using exploratory study to develop a conceptual model based upon literature review and a case study research methodology. Inductive theory-building is done by a series of survey and interview to the practitioners in higher education institution to propose key performance indicators in managing Indonesian higher education. This research is supported by theoretically and empirically proven previous frameworks performance management system applied in Indonesian higher education institutions. Time and resources constraint limits the number of higher education institutions used as empirical and observation object for this research. The significant contribution of the paper is proposing applicable key performance indicators for Indonesian higher education institution that should be as simple as possible, comprise a visual impact, focus on improvement, and be visible to everyone in the institution. This will help practitioners in higher education to recognize how they perform and as benchmarking for entire higher education institutions. Furthermore, the result of the study can support the competitiveness of Indonesian higher education in the global competition.